315 TOXOPLASMA GONDII CATHEPSIN L, TgCPL: CHARACTERIZATION AND INHIBITOR DESIGN. (1st January 2006) - Huang, R.; Hirata, K.; Bogyo, M.; Phillips, C.; Reed, S.
Abstract : Unlike most protozoa, T. gondii has a limited repertoire of clan CA cysteine proteinases, with only one cathepsin B (TgCPB), one L (TgCPL), and three cathepsin C's (TgCPC1, 2, and 3) identified in the genome project. These enzymes are attractive drug targets, as specific inhibitors of TgCPB blocked invasion in vitro and in vivo. Consequently, we cloned the cathepsin L from a cDNA library. Amino acid sequence homology was closest to the cathepsins of Sarcocystis muris (54%) and Cryptosporidium parvum (36%). The sequence contains the highly conserved ERFNIN motif of cathepsin L's with a transmembrane span. The recombinant protein was expressed as a promature enzyme in Pichia pastoris and then self-processed into the active enzyme. We have identified the preferred peptide substrates of TgCPL: Z-Phe-Arg and Z-Arg-Arg and based on these findings have begun to test biological substrates. Testing a range of pH, cathepsin L cleaves peptide substrates optimally at a pH of 6.0. E-64 inhibits > 99% of the activity of cathepsin L, consistent with its specific inhibition of cysteine proteinases. Antibodies have been developed to help localize this enzyme's site of action. We have also successfully screened an epoxide library and specific cathepsin L inhibitors are currently being used to help in further characterizing TgCPL's biological activity. Determining the crystalline structure of cathepsin L may eventually lead to targeted drug design.